Screening and Identification of Cellulase Producing Thermotolerant Fungi as Compost Starter - Rittiboon, Aree; Jatupornpipat, Marisa; Srimongkol, Piroonporn (KKU Science Journal, 2013)
The purposes of this research were to screen and identify the fungi isolated from soil having high cellulase activities for producing a compost starter. Thirty-nine isolates of fungi from soil were isolated. The primary screening of the fungi was done in the solid state medium with cellulose as the carbon source and incubated at 45°C. The ratio of the clear zone and the colonial sizes were determined. The secondary screening was done in liquid state fermentation with cellulose as the carbon source and the activities of the Carboxymethylcellulase (CMCase) were measured. The CMCase activity of the isolate FA68 was the highest and followed by that of the isolate FA50 with the enzyme activity (0.17 and 0.13. IU/ml). The isolates FA68 and FA50 were then cultivated on agricultural wastes, in solid state cultivation. The isolate FA68 grew well at 45ºC for 7 days and produced higher levels of CMCase activities compared to those of the isolate FA50 with activity 0.23 and 0.22 IU/g, respectively. When both the fungal isolates were cultivated and studied the growth in sorghum grains in order to produced as compost starter, it was found that at 37 ºC and 80 % initial moisture content, the isolates FA68 and FA50 had the highest sporulation rates of 10.27 and 9.46 log spores/g sorghum grains after 6 and 5 days incubation, respectively. Both the isolates FA68 and FA 50 were identified to be the genus Aspergillus